2021
DOI: 10.3389/fendo.2021.662769
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Body Control of Glucose Homeostasis—Insights From Model Organisms

Abstract: Tight regulation of blood glucose is essential for long term health. Blood glucose levels are defended by the correct function of, and communication between, internal organs including the gastrointestinal tract, pancreas, liver, and brain. Critically, the brain is sensitive to acute changes in blood glucose level and can modulate peripheral processes to defend against these deviations. In this mini-review we highlight select key findings showcasing the utility, strengths, and limitations of model organisms to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 154 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…In addition to different threonine and glycine levels, we found that rectal glucose differs significantly even if both species are maintained on the same diet. In insects, both diet and sugar metabolism can significantly affect glucose levels [ 42 44 ]. Given that both species were fed the same diet, we speculate that differences in glucose metabolism and transport efficiency might be the reason for different rectal glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to different threonine and glycine levels, we found that rectal glucose differs significantly even if both species are maintained on the same diet. In insects, both diet and sugar metabolism can significantly affect glucose levels [ 42 44 ]. Given that both species were fed the same diet, we speculate that differences in glucose metabolism and transport efficiency might be the reason for different rectal glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating blood glucose needs to be controlled so that there is neither hypoglycemia nor hyperglycemia, both of which are highly harmful to the body [36] [37] [38]. The blood glucose control system first involves the brain as a central control, then the HPA axis, liver, pancreas, Gut-brain axis, and the skeletal muscles that also act in case of lack of glucose from the normal controlled circuit liver-pancreas.…”
Section: Control Systemmentioning
confidence: 99%
“…As a critical component of the body's fundamental health system, glucose is a vital source of energy for people's everyday activities. 1,2 Excessive glucose levels within the body are the primary reason of diabetes and its complications, as well as several other disorders. 3,4 Accordingly, accurate and reliable detection of glucose is of great significance in biotechnology, clinical and pharmaceutical diagnostics, etc.…”
mentioning
confidence: 99%